(untitled) (Conferencea, 2023)
Today, the use of plant resources is increasing significantly. Plant raw materials are grown to provide food, including meat, dairy products and other products to the growing population. In this regard, the evaluation of the physiological, biochemical and haloaccumulating properties of new crop species, whose productivity and nutrition are not inferior to traditional species in saline and arid regions, and their introduction into agricultural practice, is of scientific and practical importance in effectively solving several agroecological problems. In the world, scientific research is being conducted on the problem of using the gene pool of plant resources, especially biodiversity in ensuring ecological stability, high nutrition and productivity of agriculture.